A roadmap towards green packaging: the current status and future outlook for polyesters in the packaging industry. Issue 20 (25th September 2017) - Rabnawaz, M.; Wyman, I.; Auras, R.; Cheng, S.
Abstract : Approximately 99% of the plastics used in the packaging industry today are petroleum-based. However, the adoption of biobased plastics could help to greatly reduce the environmental footprint of packaging materials and help to conserve our non-renewable petroleum resources. This tutorial review provides an overview of renewable polyesters and their potential packaging materials. Abstract : Approximately 99% of the plastics produced today are petroleum-based, and the packaging industry alone consumes over 38% of these plastics. In this review, we argue that renewable polyesters can provide a key milestone as renewable plastics in the route toward green packaging. This review describes different classes of polyesters with particular regard to their potential use as packaging materials. Some of the families of polyesters discussed include poly(ethylene terephthalate) and its renewable analogs, poly(lactic acid), poly(hydroxyalkanoates), and poly(epoxy anhydrides). The synthesis of polyesters is discussed from a green chemistry perspective. A structure–property correlation among the various polyesters is also discussed. The challenges that currently hinder the widespread adoption of polyesters as leading packaging materials are reviewed. The environmental footprint and end of life scenario of polyesters are discussed. Finally, future research directions are summarized as a possible roadmap towards the widespread adoption of renewable polyesters as sustainable packaging materials.